2016
DOI: 10.1161/circep.116.003929
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Treatment Intensity, and Incremental Annual Expenditures for Patients Experiencing a Cardiac Implantable Electronic Device Infection

Abstract: Background— Because of the increasing use of cardiac implantable electronic devices (CIEDs), it is important to estimate the incidence and annual healthcare expenditures associated with CIED infections. Methods and Results— Patients with a record of an initial or replacement (full implant or generator only) CIED implant during the calendar years 2009 to 2012 in MarketScan Commercial Claims and Medicare Supplemental database were identified. CIED infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 30 publications
10
58
0
2
Order By: Relevance
“…The rate was higher for replacement as opposed to de novo implants (4.4 vs 2.9%), as reported in previous studies [12,17].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The rate was higher for replacement as opposed to de novo implants (4.4 vs 2.9%), as reported in previous studies [12,17].…”
Section: Discussionsupporting
confidence: 83%
“…A study of CDI in seven pacemaker patients in Germany estimated a mean additional hospital cost of €7091 [20]. In an administrative claims database analysis in the USA, similar in methodology to our study, the estimated incremental healthcare expenditures for patients with an infection were €44,099 ($47,885) for de novo implants and €41,913 ($45,512) for replacement patients [12].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Finally, while other studies have included diverse populations of private and publicly insured patients,[7][8][9][10][11] in which the distinction between actual payer costs and provider submitted charges may be less clear and result in inflated cost estimates, we F I G U R E 6 Adjusted length of stay and costs of inpatient lead removal, by the presence of infection. In this study, we observed an increase in complication rates beginning roughly 90 days before TV lead reoperation, and a decrease after reoperation, with a similar pattern in costs.…”
mentioning
confidence: 99%